6(m+1)=3m-3

Simple and best practice solution for 6(m+1)=3m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(m+1)=3m-3 equation:


Simplifying
6(m + 1) = 3m + -3

Reorder the terms:
6(1 + m) = 3m + -3
(1 * 6 + m * 6) = 3m + -3
(6 + 6m) = 3m + -3

Reorder the terms:
6 + 6m = -3 + 3m

Solving
6 + 6m = -3 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
6 + 6m + -3m = -3 + 3m + -3m

Combine like terms: 6m + -3m = 3m
6 + 3m = -3 + 3m + -3m

Combine like terms: 3m + -3m = 0
6 + 3m = -3 + 0
6 + 3m = -3

Add '-6' to each side of the equation.
6 + -6 + 3m = -3 + -6

Combine like terms: 6 + -6 = 0
0 + 3m = -3 + -6
3m = -3 + -6

Combine like terms: -3 + -6 = -9
3m = -9

Divide each side by '3'.
m = -3

Simplifying
m = -3

See similar equations:

| -3(a+4)=6 | | -g+6+2g=4g+4 | | 6x+7=2x-13 | | 12-1.7x=4.15 | | (x+1)+2(x-3)-5=(x+2)-(x+3)+2 | | ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) | | 2x^2+8x+n=15+n | | -(ln)(2)/x=91.2 | | F(x)=x^4+6x^3+9x^2 | | x+7*2=122 | | x+7*2= | | 3n^2+4n-4=0 | | -4/3(33=n)=12=n | | 10x-30=10 | | x+2*(x+2+2x-8)=x+1*(x+1+2x-5) | | 14x-14-4+6=0 | | (3x-1)-5(x+2)(x-2)+12=6+(2x+3) | | x^2+2xy+y^2=0ratio | | 3n^2+3n-36=0 | | 3k+16=5k+20 | | -10a+25a+5a=-40 | | f=9*6 |

Equations solver categories